1992
DOI: 10.1002/j.1460-2075.1992.tb05128.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the receptor-linked protein tyrosine phosphatase LAR: proteolytic cleavage and shedding of the CAM-like extracellular region.

Abstract: The human transmembrane molecule LAR is a protein tyrosine phosphatase (PTPase) with a cell adhesion molecule‐like extracellular receptor region. The structure of LAR hinted at its involvement in the regulation of tyrosine phosphorylation through cell‐cell or cell‐matrix interactions. We show here that LAR is expressed on the cell surface as a complex of two non‐covalently associated subunits derived from a proprotein. The LAR E‐subunit contains the cell adhesion molecule‐like receptor region, while the LAR P‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
90
1
1

Year Published

1992
1992
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(124 citation statements)
references
References 56 publications
32
90
1
1
Order By: Relevance
“…It consists of an extracellular region with three immunoglobulinlike and eight-fibronectin type III structures and a cytoplasmic region containing two tyrosine phosphatase domains (29,30). The structures of the extracellular region of LAR are motifs characteristic of cell adhesion molecules.…”
Section: Discussionsupporting
confidence: 41%
“…It consists of an extracellular region with three immunoglobulinlike and eight-fibronectin type III structures and a cytoplasmic region containing two tyrosine phosphatase domains (29,30). The structures of the extracellular region of LAR are motifs characteristic of cell adhesion molecules.…”
Section: Discussionsupporting
confidence: 41%
“…Among them, type II RPTPs are characterized by the presence of varying numbers of immunoglobulin (Ig)-like and fibronectin type III repeat (FN-III)-like domains in the extracellular regions and include LAR [9,10], PTP6 [11,12], PTPx [13], PTP/t [14], PTPa (NE-3) [15,16] and Drosophila DPTP [10]. Since these structural motifs are also utilized by cell adhesion molecules such as the neural cell adhesion molecule (N-CAM), it has been postulated that type II RPTPs might be involved in cell adhesion.…”
Section: Introductionmentioning
confidence: 45%
“…In 1992, Streuli et al (1992) reported that the LAR E-subunit was shed from the surface of HeLa cells in culture. Subsequent investigations on LAR expression in mammalian tumours and cell lines, therefore, involved the use of antibodies raised against the LAR E-subunit (Li et al, 1996;Yang et al, 1999Yang et al, , 2000 with largely negative results in the tissues examined.…”
Section: Discussionmentioning
confidence: 99%
“…Among the receptor-like PTPases, leucocyte common antigen (LAR) consists of two noncovalently bound subunits, the extracellular (E) subunit and the phosphatase (P) subunit. The 150-kDa Esubunit is composed of three Ig domains and eight Fn III domains, whereas the 85-kDa P-subunit has a short extracellular domain, a transmembrane domain and two tandemly repeated PTPase domains, 1 and 2 (Streuli et al, 1992(Streuli et al, , 1998Tsujikawa et al, 2001). Previous investigations suggest that domain 2 is structurally very similar to domain 1 and that its function may be to regulate the catalytic activity or specificity of domain 1 Streuli et al, 1990;Wang and Pallen, 1991;Nam et al, 1999).…”
mentioning
confidence: 99%